Nurses' performance in assisting women with ovarian câncer (Research, Society and Development, 2020)
Introduction: The present study aims to evaluate the gynecological cancer that currently has the highest mortality rate, the ovarian cancer. It affects all types of women, is difficult to diagnose, has little chance of cure and is a major problem for public health. Objective: To identify how nurses can, through a therapeutic plan, offer assistance aimed at quality of life for women with ovarian cancer. Methods: This is a specialized literature review, carried out between August 2019 and June 2020, which included books from the library of the Faculdade de Palmas and also from online platforms, such as Biblioteca Virtual de Saúde and Scientific Electronic Electronic Libary Online. After a thorough data collection, the data was analyzed. Results and Discussions: It was possible to reaffirm that ovarian cancer is a very complex disease that does not present significant changes in the woman's life in its initial stage, however, when it begins to spread it ends up being very fatal. In this way, it was possible to verify that nurses have a fundamental role, because through careful consultation, action plans can be built that aim at the quality of life of the female population. Final Considerations: The nurse is a fundamental part of the multidisciplinary health team and must always be updated on oncology nursing and care for the early diagnosis and treatment of ovarian cancer. Only in this way can we, together, reduce the mortality rate of this overwhelming disease.